The innovative hybrid Cell-Truss Spar Buoy Platform for moderate water depth. (1st February 2016) - Sinsabvarodom, Chana; Widjaja, Joko H.
Abstract: The Hybrid Cell-Truss Spar Buoy Platform, a relatively new technology for floating structures, is studied for the Andaman Sea, that has deeper water and fault line on the seabed, despite the dominant shallow water in Southeast Asian region. This innovative Spar Buoy Platform offers many advantages, such as lower construction cost (CAPEX), a reuse option after service life, lower decommissioning costs and is suitable for use in marginal fields. This research studies three prototype models: Mono Cell-Truss Spar, Three- and Four-Cells-Truss Spar Platforms for water depths of 200 m, 400 m and 600 m, which are subjected to a 10-year and 100-year return period sea-states. The study is focused on hydrostatic stability for stationary keeping systems; while mooring analysis, hydrodynamic analysis and analysis of the structural strength of the platform are conducted as usual in design stage. The dynamic response analyses are conducted in time domain for assessing the serviceability performance of the models. Conclusively, all prototype Spar Platforms are suitable for operation in the Andaman Sea. Nevertheless, the Hybrid Cell-Truss Spar Platforms with three cells-trusses and four cells-trusses will perform with more stability and with lower dynamic responses than that of the Mono Cell-Truss Spar Buoy Platform. Abstract : Highlights: This paper introduces the innovative Hybrid Cell-truss Spar buoy platform to improve platform dynamic stability performance. These kinds of floating structures were investigatedon their suitability for application in moderate water depthat Andaman Sea which is not longer economical for on-bottom founded platforms. All prototype Hybrid Cell-truss Spar buoy platforms meet the design code requirements. The four cell truss spar shows its superior performance to other two Spar buoy platforms.